2022
DOI: 10.3390/children9121879
|View full text |Cite
|
Sign up to set email alerts
|

Prenatal Identification of a Novel Mutation in the MCPH1 Gene Associated with Autosomal Recessive Primary Microcephaly (MCPH) Using Next Generation Sequencing (NGS): A Case Report and Review of the Literature

Abstract: Background: MCPH1 is known as the microcephalin gene (OMIM: *607117), of which the encoding protein is a basic regulator of chromosome condensation (BCRT-BRCA1 C-terminus). The microcephalin protein is made up of three BCRT domains and conserved tandem repeats of interacting phospho-peptides. There is a strong connection between mutations of the MCPH1 gene and reduced brain growth. Specifically, individuals with such mutations have underdeveloped brains, varying levels of mental retardation, delayed speech and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 22 publications
0
4
0
Order By: Relevance
“…But Naseer [ 13 ] reported that two new variants of the MCPH1 gene (c.982G > A and c.1273T > A) were discovered in individuals with microcephaly in exon 8. Papoulidis [ 14 ] observed two sequential pregnancies that were complicated by extreme microcephaly due to a homozygous mutation of the MCPH1 gene which were c.348del heterozygous from parents. The phenylalanine amino acid at position 116 of the protein is replaced by the leucine amino acid due to this mutation, which changes the reading frame and leads to an early stop codon at position 145 of the protein.…”
Section: Discussionmentioning
confidence: 99%
“…But Naseer [ 13 ] reported that two new variants of the MCPH1 gene (c.982G > A and c.1273T > A) were discovered in individuals with microcephaly in exon 8. Papoulidis [ 14 ] observed two sequential pregnancies that were complicated by extreme microcephaly due to a homozygous mutation of the MCPH1 gene which were c.348del heterozygous from parents. The phenylalanine amino acid at position 116 of the protein is replaced by the leucine amino acid due to this mutation, which changes the reading frame and leads to an early stop codon at position 145 of the protein.…”
Section: Discussionmentioning
confidence: 99%
“…In contrast, mental disabilities and mild microcephaly are seen in the case of larger mutations affecting the six exons of MCPH1 ( Trimborn et al, 2005 ; Garshasbi et al, 2006 ; Mahmood et al, 2011 ). Individuals presenting mutations in the MCPH1 gene have a head circumference below the mean, mental disabilities, developmental delays, impaired language skills and infertility, and premature chromosome condensation is considered a hallmark of this disease ( Alderton et al, 2006 ; Wood et al, 2007 ; Gruber et al, 2011 ; Liu et al, 2021 ; Papoulidis et al, 2022 ). Mutations in MCPH1 are proposed to link impaired DDR and MCPH occurrence ( Mahmood et al, 2011 ).…”
Section: Microcephaly Associated With Dna Damagementioning
confidence: 99%
“…When the head circumference is more than three standard deviations below the mean, it is considered a severe microcephaly ( DeSilva et al, 2017 ; Becerra-Solano et al, 2021 ). This disease can be classified as ( Tubbs and Nussenzweig, 2017 ) primary microcephaly that can be diagnosed right after birth and has a non-progressive nature, or ( Mikolaskova et al, 2018 ) secondary microcephaly that develops at later life stages and is a progressive neurodegenerative disorder ( Papoulidis et al, 2022 ).…”
Section: Introductionmentioning
confidence: 99%
“…Autosomal recessive primary microcephaly (MCPH) is a neurodevelopment condition in which the affected born with less than 3 standard deviation (SD) smaller head circumference (HC) than expected compared to other infants of the same gestational age, sex, and ethnic background [1]. MCPH is a complex neurodevelopmental condition and associated with mild to moderate mental retardation and no obvious structural abnormalities in the brain [2]. The rate of occurrence of primary microcephaly is about 1 in 10,000 in consanguineous population e.g.…”
Section: Introductionmentioning
confidence: 99%